Syariat Islam dalam Yuridis Formal: Studi atas Nanggroe Aceh Darussalam - Mardani Mardani (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2006)
The implementation of Sharia law in the Province of Nanggroe Aceh Darussalam (NAD) cannot be separated from the long struggle of the Acehnese people in their efforts to obtain special autonomy status. After enduring a tiresome struggle, the Draft Law on Special Autonomy for the Special Region of Aceh as the Nanggroe Aceh Darussalam Province was enacted into law as Law Number 18 of 2001 concerning Special Autonomy. The fundamental aspect of this law is to provide broader opportunities for the government of NAD to regulate and manage its own household affairs, including managing economic resources, exploring and empowering natural resources and human resources. Furthermore, the people of NAD are also given the opportunity to explore and implement community norms in accordance with the noble values of Acehnese society based on Islamic Sharia principles.